2001
DOI: 10.1088/0953-2048/14/7/303
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and performance of a 1.29 T Bi-2223 magnet

Abstract: The design and fabrication procedure of a laboratory-scale Bi-2223 tape superconducting magnet with a bore of 40 mm and a maximum field of 1.29 T at 4.2 K is presented. The magnet comprises six resin impregnated double-wound pancakes of bore diameter 40 mm fabricated via the react-and-wind route. Critical current density (J c ) measurements have been made as a function of magnetic field, angle and strain at 4.2 K and 77 K on short samples. In zero field, the critical current density for the superconducting cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The coil is a basic unit for a magnet used in a maglev demonstration vehicle [7]. The coil is designed primarily for a non-eddy current structure, therefore any usage of metallic material is absent from the main structure including the copper bobbin, which is frequently used not only as a skeleton but also as a cooling path in some DC magnets [8][9][10]. The absence of the bobbin in this design also shortens the distance between the iron core and HTS coils, and thereby reduces the flux leakage as much as possible.…”
Section: Hts Coil Design and Fabricationmentioning
confidence: 99%
“…The coil is a basic unit for a magnet used in a maglev demonstration vehicle [7]. The coil is designed primarily for a non-eddy current structure, therefore any usage of metallic material is absent from the main structure including the copper bobbin, which is frequently used not only as a skeleton but also as a cooling path in some DC magnets [8][9][10]. The absence of the bobbin in this design also shortens the distance between the iron core and HTS coils, and thereby reduces the flux leakage as much as possible.…”
Section: Hts Coil Design and Fabricationmentioning
confidence: 99%
“…Following the development of the over pressure processing technique, the critical current I c (self-field) of the tape has been significantly improved by a factor of 30-40% [1,2], reaching a value of 200 A in 77 K. When the tape is used in applications, an auxiliary way is often used to increase the I c further by introducing ferromagnetic shielding (FS), which can guide the flux away from the superconductor region. In [3][4][5][6], iron yokes installed at the end of the coil were used to reduce the field at the outmost pancake, a place exposed to the strongest perpendicular field. This technique was also widely adopted in tape applications.…”
Section: Introductionmentioning
confidence: 99%
“…The substantially increased current-carrying capacity and reduced I c anisotropy of Bi-2223 at decreased temperatures (20-30 K) enable the production of cryogenfree magnet systems [8,9]. Cryogen-free systems with a temperature window 20-30 K allow generating much higher magnetic fields than using liquid nitrogen; no cryogen is required, the cooling efficiency is high, and the system is much more economical than that for 4.2 K. A 1.29 T laboratory sized Bi-2223 magnet operating at 4.2 K has been fabricated from six epoxy resin impregnated double-wound pancakes of inner diameter 40 mm made by the R&W technique [10]. Cryogenfree Bi-2223 systems have been made using stacked pancake coils producing fields of 7 T [11] at around 20 K. Recently, Richens et al [12] have presented Bi-2223 coil successfully operated by conduction cooling by a two-stage cryocooler in the temperature range 12-50 K. Their thermal stability studies have shown that thermal run-away is sufficiently controlled and damage can be readily prevented.…”
Section: Introductionmentioning
confidence: 99%